Analysis of LAI in Iran based on MODIS satellite data - Fakhri Sadat fateminia; behrouz sobhani; Seyed Abolfazl Masoodian (تحقیقات کاربردی علوم جغرافیایی)
This study was performed to evaluate the extent of leaf area in Iran from (2002) to (2016) using Remote sensing. For this purpose, we extracted data collection and leaf area index for the Iranian territory from MODIS website. The database was established with programming in MATLAB software to perform mathematical and Statistical calculations repeated. After the analysis of the data in this software a monthly average long-term map was developed. The maps show that the central, East and South-East are almost empty of leaf area or seen very sparse in some areas. In contrast areas of leaves in the northern and western parts of Iran, are good, which generally includes fields, except forest Arasbaran and Hirkany. Precipitation and the temperature, is the main factors for the growth and development of plants, that these two conditions are enumerated in the west due to being on the way of westerly winds. Lowest leaf area index is for January and February and the highest average of leaf area is for May and June. Next, study of 15 years of leaf area index data by cluster analysis based on the calculation of Euclidean distance and Ward method, showed that all 12 months fit in the two main groups and, in fact, divided for two periods of strong and weak vegetation. In this analysis, , April during the cold period and October in the warm period of the year as the transition months and they are located on a separate cluster